Doing public health differently: How can public health departments engage with local communities through social media interventions? - Megan Watkins; Jaimee S. Mallion; Daniel Frings; Jane Wills; Susie Sykes; Andrew Whittaker (Elsevier, 2023)
Objectives: This paper evaluates a collaborative intervention between public health professionals and local social media administrators, in which the social media site Facebook was used with a view to strengthening engagement with and, dissemination of, core messages and building trust and resilience within local communities during the COVID-19 pandemic. Study design: A qualitative design was used, exploring the research question: how does collaboration between public health professionals and local social network group administrators create community engagement during a global crisis? Methods: Fourteen semi-structured interviews were conducted with public health staff and online group administrators. Data was analysed using framework analysis. Results: Collaboration between public health professionals and local group administrators created both opportunities and challenges. Local group administrators had wide reach and trust within the local community, but message credibility was enhanced through local authority involvement. Such collaborations contain inherent tensions due to perceived risks to social capital and independence but can be successful if receiving strong risk-tolerant support from the local authority. Findings are discussed in the context of Bourdieu's theory of social capital to examine how public health information can be delivered by trusted social media actors in communication tailored to the local community. Conclusions: Social media provides new channels of communication for delivery of public health messages, enabling new ways of working which create long-term engagement and community building. Although the intervention was developed quickly in response to the COVID-19 pandemic, participants felt it could be mobilised to address a wider range of issues.